Code-switching: Types and Functions in Fathia Izzati's Vlog - Citra Umara Trisnayanti; Laily Nur Affini (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2021)
Abstract. This study analyzed the code-switching used in Fathia Izzati's YouTube videos channel according to the types and their functions. This study used a qualitative descriptive method since the research object is obtained from the internet or computer-based. The researchers used content analysis to get information based on research objectives. In collecting the data, the researchers analyzed the data through some steps, and they were: watching the videos, making transcription from the videos, identifying and classifying the utterances. As a result, from Fathia Izzati's videos, this study found three types of code-switching: inter-sentential switching, intra-sentential switching, and tag-switching. The speaker used two languages, namely Indonesian and English, during the vlog shooting process. The dominant type of code-switching that the speaker used is intra-sentential switching. Then, from the seven functions, this study found six functions the speakers did the code change. They were participant, solidarity, topic switch, switching for affective functions, metaphorical switching, and lexical borrowing.Keywords: bilingualism, sociolinguistics, code-switching, and video-blogging.Abstrak. Penelitian ini menganalisis alih kode yang digunakan dalam video di saluran YouTube Fathia Izzati berdasarkan jenis dan fungsinya. Penelitian ini dilakukan melalui metode kualitatif deskriptif, karena objek pada penelitian ini diambil dari internet atau bersumber dari komputer. Peneliti menggunakan analisis konten untuk menemukan informasi yang tepat sesuai dengan pertanyaan dalam penelitian ini. Dalam mengumpulkan data, peneliti menganalisis data melalui beberapa langkah, yaitu menonton dan mendengarkan video, membuat transkripsi dari video, mengidentifikasi dan mengklasifikasikan ucapan Fathia Izzati. Hasilnya, dari video-video Fathia Izzati, penelitian ini menemukan bahwa terdapat tiga tipe code-switching, di antaranya adalah inter-sentential switching, intra-sentential switching, dan tag-switching. Jadi pembicara menggunakan dua bahasa yaitu bahasa Indonesia dan bInggris selama proses syuting vlog. Jenis alih kode yang paling dominan adalah intra-sentential switching. Peneliti menemukan bahwa dari tujuh fungsi yang ada, ditemuakan enam fungsi alih kode yang dilakukan pembicara, yaitu partisipan, solidaritas, pergantian topik, peralihan karena fungsi afektif, alih kode metaforis, dan kata pinjaman.Kata kunci: bilingualisme, sosiolinguistik, alih kode, video-blogging